2010
DOI: 10.1007/s00261-010-9604-x
|View full text |Cite
|
Sign up to set email alerts
|

Retained placental tissue: role of MRI findings in diagnosis and clinical assessment

Abstract: MRI is useful for diagnosis and follow-up of RPT. The evaluation of extent of RPT attachment to the myometrium and vascularity on MRI can help the clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…13) and can help determine which are more likely to spontaneously pass by determining the surface area of attachment. 52 A small study showed that an attachment area of less than a semicircle indicated that the retained placenta was more likely to pass spontaneously. 52 Another study postulated that delayed enhancement between the retained placenta and myometrium was thought to correspond to decidua basalis, and thus, if this was absent, then the etiology of the retained placenta was accreta.…”
Section: Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…13) and can help determine which are more likely to spontaneously pass by determining the surface area of attachment. 52 A small study showed that an attachment area of less than a semicircle indicated that the retained placenta was more likely to pass spontaneously. 52 Another study postulated that delayed enhancement between the retained placenta and myometrium was thought to correspond to decidua basalis, and thus, if this was absent, then the etiology of the retained placenta was accreta.…”
Section: Managementmentioning
confidence: 98%
“…52 A small study showed that an attachment area of less than a semicircle indicated that the retained placenta was more likely to pass spontaneously. 52 Another study postulated that delayed enhancement between the retained placenta and myometrium was thought to correspond to decidua basalis, and thus, if this was absent, then the etiology of the retained placenta was accreta. 53 A recent study showed that, in postembolization patients, decreased placental enhancement in the early postcontrast phase correlated with faster resorption.…”
Section: Managementmentioning
confidence: 98%